The Dark (or the Light) Side of The Moon? Michigan's Elimination of the Local Property Tax - C. Philip Kearney (Educational Considerations, 1994)
For some, Senate Bill 1 was a bold and courageous move that held hope not only of breaking the twenty year legislative impasse on school finance reform, but also of providing a once-in-a-lifetime opportunity to reform public education.